Right-sizing Proactive Chat Reference Service Using Trigger Time. Issue 3 (2nd October 2021) - Costello, Laura; Kimura, Amy
ABSTRACT: Proactive chat service actively invites users to engage with a librarian via a pop-up chat box. While research shows that introducing proactive service in academic libraries increases the volume and complexity of chat interactions, several variables can impact its implementation in ways that are not yet well understood. Timing of the pop-up chat box is among those variables. This quantitative study investigates the effects of timing on proactive chat service through testing various pop-up trigger times on chat question volume and complexity. Results indicate a correlation between shorter trigger times with increased question volume and longer trigger times with higher question complexity at one large, multi-library research university. The findings suggest that libraries may be able to use trigger time as a control for question volume and complexity to manageably implement this high-impact service.